Program Outbound Capacity Building dalam Peningkatan Kualitas Produktivitas Karyawan - RR. Hesti Setodyah Lestari; Andia Kusuma Damayanti; Sinollah; Imron Rosyadi Hamid (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2023)
An organization can develop and continue to adapt to changes in the organizational environment, HR Capacity Building is something that absolutely must go well. In general, Capacity Building can be interpreted as a process of increasing the knowledge and skills, attitudes and behavior of human resources. Capacity Building and development is a process that is carried out at three levels, namely individuals, groups and institutions or organizations, and aims to ensure organizational continuity through achieving the goals and objectives of the organization concerned. In the outbound  program given to employees of Kopmen Setia Budi Wanita Malang East Java, with the aim that human resources have a capacity that continues to grow, the process can be carried out starting from selection, providing an adequate work environment, as well as continuous training in important aspects, such as communication skills, self-motivation, problem solving skills, creativity, and leadership. This activity received a positive response from all employees. Everyone attended and participated in the activity. Employees really hope that activities like this can be carried out periodically or periodically to refresh energy and mindset in order to gain motivation and increase employee performance productivity so that it is in line with the targets that must be achieved by the Institution